2004
DOI: 10.1210/jc.2003-031406
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenesis Therapy for Endometriosis

Abstract: It is known that angiogenesis is of pivotal importance for the development of endometriosis. However, in the treatment of endometriosis patients, prevention of endometriosis lesion development only will not be sufficient as a therapy. Treatment options, aimed at interfering with established lesions, have to be developed. In this study we evaluated whether inhibition of angiogenesis by angiostatic therapy is also effective in antagonizing the sustentation of endometriosis. We evaluated the effect of the angiost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
174
0
6

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 219 publications
(185 citation statements)
references
References 30 publications
5
174
0
6
Order By: Relevance
“…In this context, previous work by our group (Ferrero et al 2010) and other authors (Cristina et al 2005) has shown that cell populations expressing DRD2 (granulosa or pituitary cells) inhibit the secretion of VEGF in either an autocrine or a paracrine fashion. In this regard, it is known that most immune cell subtypes express DRD2 (McKenna et al 2002), and among them, macrophages are known to express large amounts of VEGF (Nap et al 2004). Moreover, the ability of macrophages to reduce angiogenesis when activated by dopamine has recently been described (Chakroborty et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this context, previous work by our group (Ferrero et al 2010) and other authors (Cristina et al 2005) has shown that cell populations expressing DRD2 (granulosa or pituitary cells) inhibit the secretion of VEGF in either an autocrine or a paracrine fashion. In this regard, it is known that most immune cell subtypes express DRD2 (McKenna et al 2002), and among them, macrophages are known to express large amounts of VEGF (Nap et al 2004). Moreover, the ability of macrophages to reduce angiogenesis when activated by dopamine has recently been described (Chakroborty et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The growth of newly formed blood vessels is of pivotal importance in the development of endometriosis (Nap et al 2004). Angiogenesis involves complex molecular interactions between endometrial tissue, peritoneal tissue, infiltrating leucocytes, and fibroblasts (Hull et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is therefore possible that if at least some growths in women become innervated, then variations in the characteristics of this innervation, such as the type and density of afferent fibers, may be the more important variable. Such afferent and efferent innervation could also contribute to maintenance of the growths, and thus, like emerging treatments aimed at reducing vascularization of ectopic endometrial growths (47,48), represent additional new avenues for treatment.…”
Section: Discussionmentioning
confidence: 99%